Enabling Systems Innovation in Climate Change Adaptation: Exploring the Role for MEL - and Gregorowski, Robbie; Bours, Dennis (Transformational Change for People and the Planet: Evaluating Environment and Development, 2022)
Traditional monitoring, evaluation, and learning (MEL) approaches, methods, and tools no longer reflect the dynamic complexity of the severe (or “super-wicked”) problems that define the Anthropocene: climate change, environmental degradation, and global pandemics. In late 2019, the Adaptation Fund’s Technical Evaluation Reference Group (AF-TERG) commissioned a study to identify and assess innovative MEL approaches, methods, and technologies to better support and enable climate change adaptation (CCA) and to inform the Fund’s own approach to MEL. This chapter presents key findings from the study, with seven recommendations to support a systems innovation approach to CCA:1.Promote and lead with a CCA systems innovation approach, engaging with key concepts of complex systems, super-wicked problems, the Anthropocene, and socioecological systems.2.Engage better with participation, inclusivity, and voice in MEL.3.Overcome risk aversion in CCA and CCA MEL through field testing new, innovative, and often more risky MEL approaches.4.Demonstrate and promote using MEL to support and integrate adaptive management.5.Work across socioecological systems and scales.6.Advance MEL approaches to better support systematic evidence and learning for scaling and replicability.7.Adapt or develop MEL approaches, methods, and tools tailored to CCA systems innovation.